Orthographic similarity ratings for English-Spanish cognates from the academic word list - Hout, Michael C.; Montelongo, Jose; White, Bryan L.; Hernandez, Anita; Serrano-Wall, Francisco (Frontiers in Education, 2023)
Cognates are words that are orthographically and semantically identical (or similar) between languages. The purpose of Experiment 1 was to provide educators and researchers with orthographic similarity ratings for the English-Spanish cognate words that comprise the Academic Word List (Coxhead, 2000). To this end, similarity ratings for the 473 English- Spanish cognate pairs were collected from 42 students enrolled in literacy education courses at a southwestern university. Experiment 2 was conducted to validate the ratings from Experiment 1 using reaction time. We found that the orthographic similarity ratings were strongly correlated with reaction times during this task lending support to the usefulness of the transparency ratings obtained in Experiment 1. Thus, educators and researchers can avail themselves of these ratings to create leveled educational materials for language instruction or to statistically calibrate experimental stimuli for learning and memory investigations. Additionally, we report an initialletter effect, which describes the finding that the earlier an English word deviates from its Spanish cognate, the lower the similarity rating for the cognate pair, thus extending the generalizability of the initial-letter effect observed by Montelongo, Hernández, Herter, & Hernández (2009).